PERAN BAITUL MAAL WAT TAMWIL AL-ITTIHAT DALAM MENINGKATKAN USAHA NASABAH DI KOTA DURI - mariatul fitri; Muhammad Yusuf (Finest : Jurnal Riset dan Pengembangan Ekonomi Islam, 2020)
The problem in this research is, how is the role of Baitul Maal Wat Tamwil Al-It seen in increasing the customer's business in Duri, what efforts have been made by the BMT in seeking to increase the business of customers who use BMT services in Duri. The objectives to be achieved in this study are to see the role of Baitul Maal Wat Tamwil Al-Ittihat in increasing customer business in Duri. The results obtained in this study indicate that the role of Baitul Maal Wat Tamwil Al-It is seen in improving customer business in Duri, the efforts made by BMT contain motivation and advice given to customers to keep circulating the capital provided by BMT. business improvements that can be recognized by BMT with smooth payments from customers. The efforts made by BMT employees in seeking to increase customers' businesses using BMT services in Duri, by continuing to provide financing to customers in the form of business capital injections, promotion efforts by BMT, improving customer performance both from the trade sector or the agricultural sector.Keywords: Role, Baitul Mal Waltamwil, Improvemen